Etiologi Multipel dari Xerostomia yang Dialami Pasien dengan HIV Positif: Studi kasus - Anzany Tania Dwi Putri (Yayasan Pendidikan Medika Indonesia, 2023)
Xerostomia is commonly reported as an oral complaint among dental patients. Many factors contribute to its presence, including medication use, chronic diseases, and psychogenic conditions. A strong association between extensive dental caries and oral infections has been discussed in several studies. Here we report a case of xerostomia related to various medical issues in a patient who was currently undergoing a 6-month rehabilitation program. Case Presentation: A 45-year-old male patient with histories of multiple substance abuse, HIV positive, Hepatitis C, and schizoaffective disorder came with a chief complaint of excessive dry mouth in the last two months. At clinical examination, poor oral hygiene with debris coated on the tongue, fissures in lip corners, little saliva amount, shiny oral mucosa, multiple carious lesions, and missing teeth were revealed. The patient was given education on how to maintain oral hygiene, asked to increase fluid intake, use 0.9% sodium chloride mouthwash every two hours daily, and scheduled weekly to receive dental treatments. Discussion: Proliferation of HIV-infected CD8+ cells and infiltration of HCV to salivary glands, drug-induced vasoconstriction, and consuming numerous medications that inhibit salivary production are suspiciously associated with the occurrence of Xerostomia. Conclusion: Comprehensive treatment that requires teamwork between dentists, physicians, and patients is strongly needed to obtain a good result.